2019
DOI: 10.3389/fmicb.2019.01638
|View full text |Cite
|
Sign up to set email alerts
|

Amoxicillin Administration Regimen and Resistance Mechanisms of Staphylococcus aureus Established in Tissue Cage Infection Model

Abstract: Staphylococcus aureus is a zoonotic pathogen that causes various life-threatening diseases. The mechanisms of action of amoxicillin against S. aureus are unclear. Here, we established a rabbit tissue cage infection model to evaluate the relationship between the pharmacokinetic/pharmacodynamic (PK/PD) parameters of amoxicillin and selective enrichment of resistant strains of S. aureus and to elucidate the evolution of its resistance to amoxicillin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The RT-qPCR data demonstrated that the expression of femX, mepA and norA have significantly increased in chromium and a lower-dose of amoxicillin pre-exposed S. aureus compared to unexposed bacteria. These findings were supported by previous studies with different bacteria, heavy metals and antibiotic co-exposure settings (9, 45, 46). Moreover, previous study also demonstrated that at metabolic stress condition, cell transporters especially efflux pumps, antiporters remove heavy metals and antibiotics from cells in a cross-resistance manner, which is known as cross-regulation (2).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The RT-qPCR data demonstrated that the expression of femX, mepA and norA have significantly increased in chromium and a lower-dose of amoxicillin pre-exposed S. aureus compared to unexposed bacteria. These findings were supported by previous studies with different bacteria, heavy metals and antibiotic co-exposure settings (9, 45, 46). Moreover, previous study also demonstrated that at metabolic stress condition, cell transporters especially efflux pumps, antiporters remove heavy metals and antibiotics from cells in a cross-resistance manner, which is known as cross-regulation (2).…”
Section: Discussionsupporting
confidence: 89%
“…25mL Tryptone soya Agar (TSA) plates were prepared for each condition. Then the 202 autoclaved 25mL TSA was transferred and 0.06μg/mL, 0.125μg/mL, 0.25μg/mL, 203 0.5μg/mL, 1.0μg/mL, 2.0μg/mL, 4.0μg/mL concentration of antibiotics were added 204 into the conical flasks (Yao et al, 2019). The control media contained no antibiotic.…”
Section: Evaluation Of Minimum Inhibitory Concentration Using Agar Di...mentioning
confidence: 99%
See 1 more Smart Citation
“…isolate was resistant to amoxicillin and azithromycin, and two isolates were resistant to both. Amoxicillin resistance in Staphylococcus aureus may be due to the expression of the femX gene, which results in continuous repairing or abnormal thickening of cell walls, (Yao et al 2019). Resistance in Streptococcus spp.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Among the most suitable reference genes for the ticagrelor treatment experiment reported by comprehensive analysis, gapdH plays an important role in glycolysis and is used frequently as a reference gene in different experimental conditions, including in an experiment that studied the resistance mechanism of S. aureus against amoxicillin [ 22 , 39 , 40 ]. Gene gyrA takes part in replication and has also been found to be a suitable reference gene for ethidium treatment experiments [ 15 ].…”
Section: Discussionmentioning
confidence: 99%